CHEMICAL ANALYSIS OF NEW RECORDED SPECIES Acalypha australis L. AT IRAQ - I. A.M. Al-Dobaissi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to chemical analysis of new recorded species Acalypha australis L. Plant samples collected from cultivated gardens and fields as well as road sides. This plant is annual herbs or weed, with wiry stem and simple lanceolate green leaves, and unisexual flowers with special cordate bracts, male flower characterized by separated anther sacs, fruits schizocarpic with 2 or 3 mericarps, pollen grains are 3-4-zonocolporate with irregular granulated sculpturing. Extract revealed a variable gropes of an important bioactive compounds as benzuquinones and its derivatives 2,6-dimethoxy – 1,4- benzoquinones which has an important roles as antioxidants compounds, From anthraquinones group the plant has trihydroxyanthraquinones with various biological and environment effects, other antioxidant compounds found in plant as phenols group represented by brevifolin carboxylic acid, gallic acid and some of its derivatives as protocatechuic acid, flavonoids compounds as rutin and kaempferol, and terpenoid as loliolide compound. Chemical analysis elucidated another compounds as phytostroles (β-sitosterol and daucosterol), butanedioic acid, and niacin.